2014
DOI: 10.1016/j.bandc.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of processes supporting memory for faces

Abstract: The retrieval processes supporting recognition memory for faces were investigated using event-related potentials (ERPs). The focus for analyses was ERP old/new effects, which are the differences between neural activities associated with correct judgments to old (studied) and new (unstudied) test stimuli. In two experiments it was possible to identify three old/new effects that behaved as neural indices of the process of recollection. In both experiments there was one old/new effect that behaved as an index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
(112 reference statements)
3
19
0
Order By: Relevance
“…3: background-exclusion task). These figures show two main peaks similar to those previously reported for recognition tasks using non-famous faces (e.g., Guillaume et al, 2012a,b;Guillaume and Tiberghien, 2013;MacKenzie and Donaldson, 2009;Yick and Wilding, 2014;Yovel and Paller, 2004). They correspond to the ERP recognition effects usually described in the literature as FN400 or mid-frontal old-new effect (300-500 ms) and the late positive component (LPC) corresponding to the parietal old-new effect (500-800 ms).…”
Section: Erp Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…3: background-exclusion task). These figures show two main peaks similar to those previously reported for recognition tasks using non-famous faces (e.g., Guillaume et al, 2012a,b;Guillaume and Tiberghien, 2013;MacKenzie and Donaldson, 2009;Yick and Wilding, 2014;Yovel and Paller, 2004). They correspond to the ERP recognition effects usually described in the literature as FN400 or mid-frontal old-new effect (300-500 ms) and the late positive component (LPC) corresponding to the parietal old-new effect (500-800 ms).…”
Section: Erp Resultssupporting
confidence: 86%
“…In a similar design, MacKenzie and Donaldson (2007); MacKenzie and Donaldson (2009) obtained yet a different set of electrophysiological outcomes, finding that the mid-frontal old-new effect (300-500 ms) reflected recollection of contextual details (occupation or other details), whereas the posterior effect, in the same epoch, was statistically equivalent whether or not contextual details were recovered. More recently, Yick and Wilding (2014) presented findings comparable to those of MacKenzie and Donaldson (2007) with a manipulation of face-intrinsic features (e.g., a white bar superimposed on the face: eyes vs. mouth). In the early epoch (300-500 ms), they reported that frontal modulation was larger when accompanied by memory for context, whereas a posterior distributed modulation was of equal size for all recognized faces.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations